Optimization of the use of sorghum flour, peanuts, and moringa leaves in the making of high-protein gluten-free biscuits [Optimasi penggunaan tepung sorgum, kacang tanah dan daun kelor pada pembuatan biskuit non-gluten tinggi protein] - Wulandari, Endah; Indiarto, Rossi; Arifin, Heni Radiani; Talitha, Shabrina Gitta (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Protein is one of the macronutrients that the body needs in large quantities in addition to carbohydrates and fats. Eating high-protein biscuits can be one way to meet daily protein needs. Biscuits made from sorghum flour, peanuts, and Moringa leaves can produce non-gluten biscuits high in protein. This study aimed to determine the optimal balance of using sorghum flour, peanuts, and moringa leaves to produce high-protein biscuits with acceptable sensory values. The research method used is an experimental method with descriptive data analysis. The optimization method uses the Response Surface Methodology (RSM) experimental design with a central composite design (CCD). The best biscuit formula, as a result of the RSM experimental design optimization, has a protein nutrient content of 8.71%, 2.60% moisture content, 2.60% ash content, 32.99% fat content, and 53.85% carbohydrate content. The combination of using flour significantly affects the texture of the biscuits but does not significantly affect the color. Using composite flour consisting of 60% sorghum flour, 37% peanuts, and 4% moringa leaves to manufacture non-gluten biscuits can produce biscuits that are high in protein and have physicochemical properties and good sensory acceptability.